1998
DOI: 10.1097/00001648-199803000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis and Organic Solvents

Abstract: To evaluate prospectively the effect on mortality of wine drinking in Eastern France, we conducted an analysis on 34,014 consecutive middle-aged men coming for a comprehensive health appraisal between 1978 and 1983. We evaluated education, physical activity, smoking, and drinking habits by a questionnaire. Electrocardiogram, blood pressure, serum total cholesterol, and gamma-glutamyltransferase level were routinely measured. Seventy-seven per cent of the subjects drank wine; there was little difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(27 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…Epidemiological studies 30,74,82 Immunological trigger for inflammatory demyelination 138 Organic solvents Epidemiological studies [139][140][141] Damage to blood-brain barrier 142 Diet Epidemiological studies 41,[143][144][145][146] vitamin D supplementation from oily fish 41 *The evidence is conflicting.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Epidemiological studies 30,74,82 Immunological trigger for inflammatory demyelination 138 Organic solvents Epidemiological studies [139][140][141] Damage to blood-brain barrier 142 Diet Epidemiological studies 41,[143][144][145][146] vitamin D supplementation from oily fish 41 *The evidence is conflicting.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Consequently, search for natural additives, especially of plant origin, has notably increased. Epidemiological studies have also indicated that frequent consumption of natural antioxidants is associated with a lower risk of cardiovascular disease and cancer (Renaud et al, 1998; Temple, 2000). The defensive effects of natural antioxidants in fruits and vegetables are related to three major groups: vitamins, phenolics, and carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have indicated an inverse correlation between red wine consumption and the risk of cardiovascular diseases [1,2,3]. The protective effect of red wine on the cardiovascular system is due, at least in part, to the polyphenolic component [4].…”
Section: Introductionmentioning
confidence: 99%